Modeling the two-stage anaerobic digestion of domestic wastewater with the development of a monitoring application - Vega De Lille, Marisela Ix Chel; Forstner, Judith; Groß, Frauke; Benning, Rainer; Delgado, Antonio (BRAZ J CHEM ENG, 2016)
The IWA Anaerobic Digestion Model No. 1 (ADM1) was chosen to simulate a two-stage anaerobic digestion lab-scale plant treating domestic wastewater. Initially, the model was preliminary tested using synthetic wastewater. The simulation results were satisfactorily compared to NH4+ and chemical oxygen demand (COD) data for the first and second stages, respectively. A transformation method was then applied to estimate from the domestic wastewater composition the input variables to the ADM1. After proper calibration and further validation, the model was able to successfully predict the COD degradation from a varying influent, showing its practical applicability. Finally, a standalone application based on the validated model was developed to be used for monitoring purposes at the treatment plant. The developed application is suitable for direct implementation at a full-scale plant without the need of additional software or specialized assistanc
UnivIS-Import:2018-02-22:Pub.2016.tech.ITC.stmmec.modeli
Keywords: Mathematical modeling; Domestic wastewater; ADM1; Standalone application; Two-stage anaerobic digestion